A novel design method for 3D positive and negative Poisson's ratio material based on tension-twist coupling effects. (15th March 2020) - Duan, Shengyu; Xi, Li; Wen, Weibin; Fang, Daining
Highlights: A novel 3D NPR material design method based on the tension-twist coupling effects have been proposed. Eleven types of novel 3D lattice materials with NPR and PPR properties are proposed. The numerical and experimental results show that the proposed novel 3D NPR and PPR materials exhibit desirable PR properties. Abstract: In recent years, as the development of additive manufacturing technology, 3D negative Poisson's ratio (NPR) materials attract many researchers' interest. In this paper, a novel 3D NPR material design method based on the tension-twist coupling effect has been proposed. A novel category of 3D NPR and positive Poisson's ratio (PPR) materials by linking multilayer 2D NPR materials through 3D chiral chains are proposed. The sign of the Poisson's ratio depends on the linkage pattern of the 3D chiral chain. Based on this method, 11 types of novel 3D NPR and PPR materials are presented. Experimental and numerical methods are adopted to study the mechanical properties of the proposed novel 3D NPR and PPR materials. Results show that the novel 3D materials present desirable NPR and PPR as we expected, which proved the effectiveness of the proposed design method.